Traversing multicultural and multilingual educational landscapes in Odisha, India: the impact of adaptive performance, cultural intelligence, and transformational leadership on foreign language teacher wellbeing - Behera, Rashmi Ranjan; Ramasami, Karthik; Acharya, Amulya Kumar; Sharma, Saurabh; Subhrajyoti, Trupti; Tikader, Bikram (Frontiers in Education, 2025)
Teacher wellbeing (TWB) among foreign language teachers (FLTs) remains an overlooked area in educational research, despite their critical role in fostering linguistic and cultural competence. FLTs face unique challenges, particularly in multilingual and multicultural regions, which can significantly impact their wellbeing. This study examines the interrelationships among FLTs' adaptive performance (AP), cultural intelligence (CQ), and principals' transformational leadership (TL) in shaping TWB. Focusing on six border districts of Odisha, India, where FLTs operate within a multicultural and multilingual educational landscape, this study employs a quantitative research design to propose and test seven hypotheses. Data collected through a structured questionnaire from FLTs across these districts were analyzed using Partial Least Squares Structural Equation Modeling. Results reveal that AP, CQ, and TL significantly influence TWB. Moreover, CQ acts as a complementary partial mediator between AP and TWB and between TL and TWB, indicating that AP enhances TWB not only by equipping teachers with the flexibility to manage professional challenges but also by fostering intercultural competence, which further improves their work experiences. Additionally, TL plays an important role in creating a supportive and culturally responsive work environment that strengthens TWB. These insights emphasize the need for school leadership to cultivate an inclusive and adaptive educational atmosphere. While the study is region-specific and relies on self-reported data, it contributes to the understanding of TWB in multilingual and multicultural settings. The findings provide valuable guidance for policymakers and educational leaders in designing strategies to enhance both FLTs' and students' wellbeing in diverse educational contexts.